1987
DOI: 10.1002/jcp.1041300203
|View full text |Cite
|
Sign up to set email alerts
|

Conditional responsiveness of a chemically transformed cell line to growth factor stimulated DNA synthesis

Abstract: BP3T3, a clonal benzo(a)pyrene-transformed BALB/c-3T3 cell line, is conditionally responsive to growth factor stimulation. Density arrested cell populations deprived of growth factors by pretreatment with 0.5% platelet-poor plasma synthesized DNA both in response to ng/ml concentrations of PDGF, EGF, and somatomedin C, and in response to insulin, plasma, and serum. The above agents acted singly to induce DNA synthesis, but synergism is suggested because a higher percentage of cells were stimulated to enter the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It apsome plates and incubation a t 37 C continued for a n peared likely that MG-63 cells do not have a growth additional 2 h. Total RNA was isolated from the cells as requirement for PDGF. Because certain cell lines grow equally well in serum or plasma-derived serum-supplemented medium, yet can be stimulated to replicate when PDGF is added to density-arrested cultures (Whipple et al, 1987), we studied PDGF-modulated DNA synthesis in growth-arrested populations. Flow microfluorimetry revealed that about 85% of MG-63 cells became arrested with a GI DNA content 3-5 days after transfer of confluent cultures to 0.3% or 1% plasma-(or plasma-derived serum)-supplemented medium (data not shown).…”
Section: Pdgf Growth Requirement and Mitogenicitymentioning
confidence: 99%
“…It apsome plates and incubation a t 37 C continued for a n peared likely that MG-63 cells do not have a growth additional 2 h. Total RNA was isolated from the cells as requirement for PDGF. Because certain cell lines grow equally well in serum or plasma-derived serum-supplemented medium, yet can be stimulated to replicate when PDGF is added to density-arrested cultures (Whipple et al, 1987), we studied PDGF-modulated DNA synthesis in growth-arrested populations. Flow microfluorimetry revealed that about 85% of MG-63 cells became arrested with a GI DNA content 3-5 days after transfer of confluent cultures to 0.3% or 1% plasma-(or plasma-derived serum)-supplemented medium (data not shown).…”
Section: Pdgf Growth Requirement and Mitogenicitymentioning
confidence: 99%